Brown, White and Blue Bagging in Special Pharmacy: An Emerging Trend to Minimize Medication Error - Sharad Chand (Journal of Global Pharma Technology, 2019)
Advancement in the sector of specialized pharmacy evolved a new concept of bagging system beyond the scope of traditional pharmacy service. Managed care organizations (MCOs) bring up the healthcare system in the network where the services are made available for the betterment of treatment and secure documentation system for reimbursement. Certain models namely brown bagging, white bagging, and blue bagging system are promising models for this system. These models generally cover expensive and high-risk medication to minimize the wastage and related drug related problems. In these models, all the prescribed medications reach to the health professionals, which meticulously review all the medications before its administration. This potential system has several advantages over the conventional pharmacy practices, despite several advantages many associated risk and disadvantages are equally challenging. But it can be concluded that benefits are outweighing the risk associated with these models, which may have more impact on patient wellbeing. Hence, this system of special pharmacy service can be recommended in the scope of hospital pharmacy and pharmacy practice.